The Effect of Perceptions, Study Program Accreditation, and Promotion on the Decision to Choose the Air Transportation Logistics Management Study Program at Jayapura Aviation Polytechnic - Kona, Musri; Bunahri, Rifqi Raza; Supardam, Dhian; Prayitno, Hadi (Dinasti Publisher, 2023)
This study aims to identify the influence of perception, study program accreditation, and promotion on student decisions in choosing the Air Transportation Logistics Management study program at the Jayapura Aviation Polytechnic. Data were collected from 381 prospective student respondents and analyzed using multiple regression analysis. The results of the analysis show that perception (? = 0.262, p < 0.05), study program accreditation (? = 1.178, p < 0.05), and promotion (? = 0.291, p < 0.05) have a significant influence on the decision choose a study program. Study program accreditation variable has the most significant influence. Although the Air Transportation Logistics Management Study Program does not yet have study program accreditation, respondents are confident that they have chosen this study program because of the good reputation of the tertiary institution and its graduates have broad job opportunities. The recommendations for the Jayapura Aviation Polytechnic are strengthening marketing strategies with effective promotion, obtaining study program accreditation, and maintaining a good reputation. This will increase the attractiveness of the study program and meet the needs of prospective students.